CO2 Raman thermometer improvement: Comparing hot band and Stokes and anti‐Stokes Raman scattering thermometers. (7th August 2018) - Hagiwara, Yuuki; Takahata, Kohei; Torimoto, Junji; Yamamoto, Junji
Abstract: CO2 fluid inclusions are popular in the mantle‐derived rock. CO2 Raman densimeter is widely used for estimating depth provenance and magma plumbing system. However, in order to obtain precise CO2 density, we should also measure CO2 temperature simultaneously because the densimeter has temperature dependency. In this study, we measured CO2 Raman spectra with densities of 0.8–1.0 g/cm 3 at temperatures of 15, 25, 35, 45, and 55°C using a high‐pressure optical cell. We propose a new equation relating hot bands to the Fermi diad intensity ratio, temperature, and distance between the Fermi diad (delta, cm −1 ), which has higher accuracy than those of previous studies (±3.9–4.7°C) across all measurement conditions. The change in temperature engenders thermal expansion or shrinkage of mineral, resulting in change in CO2 density of fluid inclusion. Simultaneous measurement of both density and temperature of CO2 will be a probe for elastic property of minerals. Abstract : We measured CO2 Raman spectra with densities of 0.8–1.0 (g/cm 3 ) at temperatures of 15, 25, 35, 45, and 55°C using high‐pressure optical cell. We propose a new equation relating hot bands to the Fermi diad intensity ratio, temperature, and distance between the Fermi diad (delta, cm −1 ), which has higher accuracy than those of previous studies (±3.9–4.7°C) across all measurement conditions (0.8–1.0 g/cm 3 and 15–55°C).